On bargaining sets of supplier-firm-buyer games - Ata Atay; Tamás Solymosi (Hungarian Academy of Sciences, Institute of Economics, 2018)
We study a special three-sided matching game, the so-called supplier-firm-buyer game, in which buyers (customers) and sellers (suppliers) trade indirectly through middlemen (firms). Stuart (Stuart, 1997) showed that all supplier-firm-buyer games have non-empty core. We show that for these games the core coincides with the classical bargaining set (Davis and Maschler, 1967), and also with the Mas-Colell bargaining set (Mas-Colell, 1989).
Keywords: C71; 330; Bargaining set; core; matching market; assignment game; cooperative game